The effects of asymmetric regulation on the quality of broadband networks - Viktória Kocsis (International Telecommunications Society (ITS), 2013)
Network operators of competing infrastructures in European electronic communications markets face asymmetric regulation: incumbent telecommunications firms are required to open their networks for retail broadband competition, while cable companies have no such obligation. Furthermore, for historical reasons, cable companies have better quality networks thanks to the DOCSIS 3.0 technology than DSL-based telecom firms. How would the market structure of electronic communications markets and the quality of networks develop in the presence of asymmetric regulation and original quality differences? Based on a location model for product differentiation, i find that access revenues can compensate incumbent telecom firms for the loss due to having a lower quality network than cable companies. Therefore, access obligation reduces the incentives of telecom firms to compete with cable companies by upgrading network quality. In the absence of retail competitors without networks, however, telecom firms need to upgrade network quality to be able to remain competitive with cable companies. Furthermore and in line with the existing literature, the exclusion of retail competitors is more likely in the presence of higher access prices and stronger substitutuion between firms' products. Finally, if the original differences between network quality is large and high returns on investments are unlikely, telecom firms may not be able to invest sufficiently and lose substantially from their market shares.
Keywords: L51; L96; L10; K23; 330; Telecommunications; Investments; Quality; Access regulation; Asymmetric regulation